2016
DOI: 10.1097/inf.0000000000001072
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, Tolerability and Safety in Adolescents of Bivalent rLP2086, a Meningococcal Serogroup B Vaccine, Coadministered with Quadrivalent Human Papilloma Virus Vaccine

Abstract: Concomitant administration of bivalent rLP2086 and HPV-4 elicits robust immune responses to both vaccines without increasing reactogenicity compared with bivalent rLP2086 alone. Concurrent administration may increase compliance with both vaccine schedules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 20 publications
3
22
0
1
Order By: Relevance
“…This small study not only confirmed that clinical isolates tended to be more resistant to the bactericidal antibody elicited by immunization with Bexsero but that SBA activity also declined significantly within 4 to 6 months of the administration of the second dose of vaccine. Trumenba also proved to be highly immunogenic in this age group, with titers exceeding the lower limit of quantitation against its panel of reference isolates in 80% to 100% of vaccinees receiving three doses of vaccine (4951). Data from a small study of individual sera from young adults, using an antigenically diverse panel of isolates to determine SBA activity, suggest that this vaccine has the potential to offer broad protection, but this remains to be confirmed by surveillance once the vaccine is more widely used.…”
Section: Vaccine Antigen Coverage Antibody Persistence and Agementioning
confidence: 98%
“…This small study not only confirmed that clinical isolates tended to be more resistant to the bactericidal antibody elicited by immunization with Bexsero but that SBA activity also declined significantly within 4 to 6 months of the administration of the second dose of vaccine. Trumenba also proved to be highly immunogenic in this age group, with titers exceeding the lower limit of quantitation against its panel of reference isolates in 80% to 100% of vaccinees receiving three doses of vaccine (4951). Data from a small study of individual sera from young adults, using an antigenically diverse panel of isolates to determine SBA activity, suggest that this vaccine has the potential to offer broad protection, but this remains to be confirmed by surveillance once the vaccine is more widely used.…”
Section: Vaccine Antigen Coverage Antibody Persistence and Agementioning
confidence: 98%
“…For the adolescent study, individuals aged 10‐18 years enrolled at sites across North America and Europe were randomly assigned to receive MenB‐FHbp (n = 2693) or control vaccine (hepatitis A virus vaccine [HAV]/saline; n = 897) at months 0, 2 and 6 (Table ). In a similar study performed in young adults, individuals aged 18‐25 years enrolled at sites across North America and Europe were randomly assigned to receive MenB‐FHbp (n = 2471) or saline (n = 822) at months 0, 2 and 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Several phase 2 studies have assessed the immunogenicity, safety and tolerability of concomitant administration of MenB‐FHbp with quadrivalent human papillomavirus vaccine (HPV4) and with MenACWY administered concomitantly with Tdap (Table ) . The HPV4 study was performed prior to availability of the non‐avalent HPV vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…For HPV-18, noninferiority criteria (lower bound of the 95% confidence interval of geometric mean titer [GMT] ratio >0.67) were not met for the GMT ratio at 1 month after the third quadrivalent HPV vaccination (lower bound of 95% confidence interval for GMT ratio was 0.62); however, for each HPV vaccine type, more than 99% of subjects achieved seroconversion. 16 In clinical trials, both MenB vaccines were safe, with few serious adverse events (all resolved without sequelae). 7 -16 There were no deaths considered to be related to either vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…1 College students have a lower risk of serogroup B meningococcal disease than the general population of a similar age (college students compared with 18-through 23-year-olds: 0.09 per 100 000 and 0.14 per 100 000, respectively). 16 and for MenACWY and tetanus, diphtheria, and pertussis antigens (unpublished data) when MenB-FHbp was administered concomitantly. For HPV-18, noninferiority criteria (lower bound of the 95% confidence interval of geometric mean titer [GMT] ratio >0.67) were not met for the GMT ratio at 1 month after the third quadrivalent HPV vaccination (lower bound of 95% confidence interval for GMT ratio was 0.62); however, for each HPV vaccine type, more than 99% of subjects achieved seroconversion.…”
Section: Introductionmentioning
confidence: 99%